Analisis Pengungkapan Nilai Islam Dalam Laporan Tahunan Bank Syariah di Indonesia - Muhammad Praditya Mas’ud (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2013)
This research is an exploratory study aimed to assess the degree of suitability of thedisclosure information of Islamic values in the annual report of Islamic Banks (BUS)with items that duly disclosed. This research using 2010 BUS annual report. In order tomake this result of this research can be compared with other similar researches, instruction encoding, which items should be disclosed or items that duly disclosed, adaptedfrom two previous studies which have similarity with this research theme, Haniffa Hudaib (2004) and Prasetyaningsih Prakosa (2010). This study uses content analysisas an analytical tool, which makes a set of related-specific text into analysis unit. Theresults showed that some of the new BUS emerged in 2010 have not been optimallydisclose Islamic values in their annual reports. But according to the overall score, all ofBUS annual report have disclosed enough information about Islamic values that shouldbe disclosed in annual reports.